Ответы и объяснения

2013-04-16T18:21:42+00:00

62p^{2} - q^{2}=(4p-q)(4p+q)

1-81b^{2} = (1-9b)(1+9b)

16c^{2}d^{2} - 9 =(4cd-3)(4cd+3)

25q^{4} - 169t^{6} = (5q^{2} - 13t^{3})(5q^{2} + 13t^{3})

121 - (a+3)^{2} = (11-(a+3))(11+(a+3))

 

Лучший Ответ!
2013-04-16T18:22:52+00:00

1) а)(8p-q)(8p+q)

б)(1-9b)(1+9b)

в)(4cd-3)(4cd+3)

г)(5q^2-13t^3)(5q^2+13t^3)

д)(11-a-3)(11+a+3)=(8-a)(14+a)

2) (6x-13)(6x+13)=0

    6x-13=0  или 6x+13=0

    6x=13              6x=-13

     x=13\6              x=-13\6

     x=2  1\6             x=-2  1\6

Ответ: 2  1\6; -2  1\6